Correction: Why ponds concentrate nutrients: the roles of internal features, land use, and climate - Mireia Bartrons; Jing Yang; Maria Cuenca‑Cambronero; Pieter Lemmens; Maria Anton-Pardo; Meryem Beklioğlu; Jeremy Biggs; Aurélie Boissezon; Dani Boix; Clementina Calvo; Maite Colina; Thomas A. Davidson; et al. (Hydrobiologia, 2026)

Why ponds concentrate nutrients: the roles of internal features, land use, and climate - Mireia Bartrons; Jing Yang; Maria Cuenca‑Cambronero; Pieter Lemmens; Maria Anton-Pardo; Meryem Beklioğlu; Jeremy Biggs; Aurélie Boissezon; Dani Boix; Clementina Calvo; Maite Colina; Thomas A. Davidson; et al. (Hydrobiologia, 2025)
Ponds are key freshwater habitats supporting biodiversity and ecosystem services, yet they remain understudied in the context of land use and climate change. We examined 240 ponds across eight countries (seven in Europe and Uruguay) to assess how internal pond characteristics, surrounding land cover and livestock intensity, seasonal climatic variation, and climate influence nutrient concentrations across spatial and temporal scales. Nutrient concentrations were strongly associated with internal features: shallow ponds and short hydroperiods had higher total nitrogen (TN) and total phosphorus (TP) concentrations, while thermal stratification, typically found in deeper ponds, was associated with higher TN, indicating enhanced internal nutrient recycling. Land use also played a significant role with agricultural intensity increasing nutrient concentration (both TN and TP), whereas forest cover reduced TP. Seasonal variation modulated these patterns, with higher TP concentrations observed in summer, and with dilution effects during wetter and cooler periods, particularly for TN in semi-permanent ponds. These findings underscore the combined influence of physical characteristics, landscape context, and climate variability on nutrient concentrations in ponds and highlight the need for integrated, multi-scale approaches to anticipate the impacts of global climate change effects on these ecologically valuable ecosystems.

Challenges and opportunities in the use of ponds and pondscapes as Nature-based Solutions - M. Cuenca-Cambronero; M. Blicharska; J.-A. Perrin; T. A. Davidson; B. Oertli; M. Lago; M. Beklioglu; M. Meerhoff; M. Arim; J. Teixeira; L. De Meester; J. Biggs; et al. (Hydrobiologia, 2023)
Ponds and “pondscapes” (networks of ponds) are crucial habitats for biodiversity and for delivering multiple benefits to humans, so-called “Nature’s Contribution to People”, such as climate mitigation and adaptation to climate change, creation, and maintenance of habitat for biodiversity, water purification, flood mitigation and cultural benefits (e.g., recreational possibilities). However, ponds are not often considered as Nature-based Solutions to provide all these benefits. In addition, there is insufficient knowledge on how to manage and restore ponds to maximise their role to increase the resilience of ecosystems and society to climate change. To facilitate improved implementation of ponds as Nature-based Solutions for the delivery of a wide range of Nature Contributions to People, it is important to generate and integrate biodiversity, ecosystems, societal, economic and policy knowledge. Hence, there is a need for evidence-based guidance to support the broader use of ponds. Here, we review the role of ponds and pondscapes in delivering Nature’s Contributions to People and provide an overview of the challenges and opportunities for their broader implementation as Nature-based Solutions. Finally, we propose a conceptual framework that can help the implementation of pond Nature-based Solutions, and that outlines future research needs.

Carbon fluxes in subtropical shallow lakes: contrasting regimes differ in CH4 emissions - Maite Colina; Sarian Kosten; Nicolás Silvera; Juan M. Clemente; Mariana Meerhoff (Hydrobiologia, 2022)

Drivers of zooplankton beta diversity in natural shallow lakes and artificial reservoirs in the Neotropics - Nadson R. Simões; Juliana D. Dias; Mariana Meerhoff; Fabio A. Lansac-Tôha; Luis M. Bini; Claudia C. Bonecker (Hydrobiologia, 2022)

Herbivory can mitigate, but not counteract, the positive effects of warming on the establishment of the invasive macrophyte Hydrilla verticillata - Clementina Calvo; Roger P. Mormul; Bruno R. S. Figueiredo; Eduardo R. Cunha; Sidinei M. Thomaz; Mariana Meerhoff (Biological Invasions, 2019)

Fish composition and species richness in eastern South American coastal lagoons: additional support for the freshwater ecoregions of the world - A. C. Petry; T. F. R. Guimarães; F. M. Vasconcellos; S. M. Hartz; F. G. Becker; R. S. Rosa; G. Goyenola; E. P. Caramaschi; J. M. Díaz de Astarloa; L. M. Sarmento‐Soares; J. P. Vieira; A. M. Garcia; et al. (Journal of Fish Biology, 2016)
The relationships between fish composition, connectivity and morphometry of 103 lagoons in nine freshwater ecoregions ( FEOW ) between 2·83° S and 37·64° S were evaluated in order to detect possible congruence between the gradient of species richness and similarities of assemblage composition. Most lagoons included in the study were 2 , with a maximum of 3975 km 2 in surface area. Combined surface area of all lagoons included in the study was 5411 km 2 . Number of species varied locally from one to 76. A multiple regression revealed that latitude, attributes of morphometry and connectivity, and sampling effort explained a large amount of variability in species richness. Lagoon area was a good predictor of species richness except in low latitude ecoregions, where lagoons are typically small‐sized and not affected by marine immigrants, and where non‐native fish species accounted for a significant portion of species richness. Relationships between species and area in small‐sized lagoons ( 2 ) is highly similar to the expected number in each ecoregion, with systems located between 18·27° S and 30·15° S attaining higher levels of species richness. Similarities in species composition within the primary, secondary and peripheral or marine divisions revealed strong continental biogeographic patterns only for species less tolerant or intolerant to salinity. Further support for the FEOW scheme in the eastern border of South America is therefore provided, and now includes ecotonal systems inhabited simultaneously by freshwater and marine species of fishes.

Community structure of fish in lowland streams differ substantially between subtropical and temperate climates - Franco Teixeira-de Mello; Mariana Meerhoff; Annette Baattrup-Pedersen; Thomas Maigaard; Peter B. Kristensen; Torben K. Andersen; Juan M. Clemente; Claudia Fosalba; Esben A. Kristensen; Malvina Masdeu; Tenna Riis; Néstor Mazzeo; et al. (Hydrobiologia, 2012)

High predation is of key importance for dominance of small-bodied zooplankton in warm shallow lakes: evidence from lakes, fish exclosures and surface sediments - Carlos Iglesias; Néstor Mazzeo; Mariana Meerhoff; Gissell Lacerot; Juan M. Clemente; Flavio Scasso; Carla Kruk; Guillermo Goyenola; Javier García-Alonso; Susanne L. Amsinck; Juan C. Paggi; Susana José de Paggi; et al. (Hydrobiologia, 2011)

Can ephemeral proliferations of submerged macrophytes influence zoobenthos and water quality in coastal lagoons? - Lorena Rodríguez-Gallego; Erika Meerhoff; Juan M. Clemente; Daniel Conde (Hydrobiologia, 2010)

Detection of multiple respiratory pathogens during primary respiratory infection: nasal swab versus nasopharyngeal aspirate using real-time polymerase chain reaction - T. J. Meerhoff; M. L. Houben; F. E. J. Coenjaerts; J. L. L. Kimpen; R. W. Hofland; F. Schellevis; L. J. Bont (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Can warm climate‐related structure of littoral predator assemblies weaken the clear water state in shallow lakes? - MARIANA MEERHOFF; JUAN M. CLEMENTE; FRANCO TEIXEIRA De MELLO; CARLOS IGLESIAS; ASGER R. PEDERSEN; ERIK JEPPESEN (Global Change Biology, 2007)
Shallow lakes, the most abundant lake type in the world, are very sensitive to climatic changes. The structure and functioning of shallow lakes are greatly impacted by submerged plants, and these may be affected by climate warming in various, contrasting, ways. Following a space‐for‐time substitution approach, we aimed to analyse the role of aquatic (submerged and free‐floating) plants in shallow lakes under warm climates. We introduced artificial submerged and free‐floating plant beds in five comparable lakes located in the temperate zone (Denmark, 55–57 °N) and in the subtropical zone (Uruguay, 30–35 °S), with the aim to study the structure and dynamics of the main associated communities. Regardless of differences in environmental variables, such as area, water transparency and nutrient status, we found consistent patterns in littoral community dynamics and structure (i.e. densities and composition of fish, zooplankton, macroinvertebrates, and periphyton) within, but substantial differences between, the two regions. Subtropical fish communities within the macrophyte beds exhibited higher diversity, higher density, smaller size, lower relative abundance of potentially piscivores, and a preference for submerged plants, compared with otherwise similar temperate lakes. By contrast, macroinvertebrates and cladocerans had higher taxon richness and densities, and periphyton higher biomass, in the temperate lakes. Several indicators suggest that the fish predation pressure was much stronger among the plants in the subtropical lakes. The antipredator behaviour of cladocerans also differed significantly between climate zones. Submerged and free‐floating plants exerted different effects on the spatial distribution of the main communities, the effects differing between the climate zones. In the temperate lakes, submerged plants promoted trophic interactions with potentially positive cascading effects on water transparency, in contrast to the free‐floating plants, and in strong contrast to the findings in the subtropical lakes. The higher impact of fish may result in higher sensitivity of warm lakes to external changes (e.g. increase in nutrient loading or water level changes). The current process of warming, particularly in temperate lakes, may entail an increased sensitivity to eutrophication, and a threat to the high diversity, clear water state.

Restoration of shallow lakes by nutrient control and biomanipulation—the successful strategy varies with lake size and climate - E. Jeppesen; M. Meerhoff; B. A. Jacobsen; R. S. Hansen; M. Søndergaard; J. P. Jensen; T. L. Lauridsen; N. Mazzeo; C. W. C. Branco (Hydrobiologia, 2007)